Formação inicial do professor de Educação Física para o trabalho com alunos com necessidades educacionais especiais - Zini, Rodrigo (2018)
From the movement of Special Education in the perspective of Inclusive Education, more and more students with special educational needs are inserted in regular schools. In order for the attendance to this student to be of quality, it is the responsibility of the school to promote adaptations to meet the of all students, whether or not disabled. In addition, it is understood that the courses that seek to train teachers need to offer in their curricular grades theoretical and practical about special education. In that direction, the aim of this study was to verify how the initial formation of the Physical Education teacher occurs to work with students with special educational needs, inserted in common schools. A descriptive study was carried out based on a field study that involved 3 courses of degree in Physical Education of Institutions of Higher Education public and private West of Paraná. Data were collected through a documentary survey in curriculum matrices and teaching plans of the respective courses, of interviews, with 3 coordinators and 3 teachers who worked with the discipline that deals with the area of Special Education, and the application of questionnaires to 92 academics of the last period of the course. After analyzing the data, it was verified that all the courses of the sample have in their curriculum with disciplines that deal with the contents of the Special Education, to know, a discipline related to the Brazilian Language of Signs (Pounds) and another is intended to work the fundamentals of Physical Education for students with special educational needs. However, as reported by the students and teachers, these contents are insufficient, in view of the challenges presented from the inclusion of these students in regular education. It was observed that 2 courses offer research projects related to Special Education. With regard to extension activities, it was noticed that the 3 courses offer experiences with regard to students with special educational needs, but only one holds extension projects continuously. Regarding the internship supervised, it was verified that one of the courses offers the possibility of the academic perform the internship in special education schools. It was not found, during internships in regular schools, work involving the inclusion of students with special educational needs. In this sense, despite the courses, during the initial training, offer contents and experiences related to the theme of Special Education, show many difficulties in what it refers to form their academic for the work to be carried out with the target audience of Special Education, both in terms of theoretical contents and the practices that involve these students.